A Randomized Controlled Trial of Phenylephrine and Noradrenaline Boluses for Treatment of Postspinal Hypotension During Elective Caesarean Section. Issue 2 (June 2020) - Mohta, M.; Garg, A.; Chilkoti, G.T.; Malhotra, R.K.
Abstract : ( Anaesthesia . 2019;74:850–855) Phenylephrine is the preferred vasopressor for treating spinal-induced hypotension during cesarean delivery due to its rapid onset, short duration of action, and lack of adverse effects on fetal acid-base status. However, norepinephrine is often used in critical care settings, especially in patients with septic shock, and may be less likely than phenylephrine to cause bradycardia. Although several studies have been conducted in recent years on the use of norepinephrine for the treatment and prevention of spinal-induced hypotension during cesarean delivery, there are limited data comparing phenylephrine and norepinephrine in terms of safety, efficacy, neonatal outcomes, and side effects. This study aimed to compare the rate of maternal bradycardia between the 2 drugs when administered as intravenous boluses to treat hypotension during elective cesarean delivery with spinal anesthesia.